1990
DOI: 10.1037/1040-3590.2.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychopathy and release outcome in a criminal population.

Abstract: Additional construct validity of Hare's Psychopathy Checklist (PCL) was sought by comparing empirically derived predictors of recidivism with PCL scores among 93 inmates who were first released on temporary absences and subsequently followed on parole. The PCL proved to be reliable and a more efficient predictor of release outcome than an empirically derived predictive index. Psychopathy ratings predicted outcome for both temporary absence and parole release. PCL scores and actuarial prediction scales of recid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
84
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 15 publications
8
84
0
1
Order By: Relevance
“…Other studies present similarly supportive findings for the predictive and explanatory capabilities of the PCL-R for violent and recidivistic outcomes (e.g. Harris, Rice, & Cormier, 1991;Harris, Grant, & Lalumiere, 2001;Hart, Kropp, & Hare, 1988;Hemphill, Hare, & Wong, 1998;Rice, 1997;Serin, Peters, & Barbaree, 1990). …”
supporting
confidence: 50%
“…Other studies present similarly supportive findings for the predictive and explanatory capabilities of the PCL-R for violent and recidivistic outcomes (e.g. Harris, Rice, & Cormier, 1991;Harris, Grant, & Lalumiere, 2001;Hart, Kropp, & Hare, 1988;Hemphill, Hare, & Wong, 1998;Rice, 1997;Serin, Peters, & Barbaree, 1990). …”
supporting
confidence: 50%
“…The utility of the psychopathic construct has been supported in previous research in that psychopathy has been shown to designate a subgroup of adult offenders who show more chronic and severe patterns of violent and antisocial behaviors (Serin, Peters, & Barbaree, 1990). In addition, the abnormality in emotional responding that was linked only to the affective factor in psychopathy (Patrick et al, 1993;Vanman et al, 2003) suggests that affective blunting and lack of empathy may be one of the main reasons why individuals high in psychopathic traits commit aggressive and antisocial behavior.…”
mentioning
confidence: 60%
“…Research has shown that being high in psychopathic traits is most likely to be associated with violence and criminality (Serin et al, 1990).…”
Section: Similarities and Differences Among The Three Personality Conmentioning
confidence: 99%
“…In the community, psychopaths are responsible for committing over 50% of the most violent crimes (Hare, 1993), and high levels of psychopathic traits are strong predictors of chronic offending, antisocial behavior (Baskin-Sommers, Baskin, Sommers, & Newman, 2013;Blais, Solodukhin, & Forth, 2014), and recidivistic risk (DeMatteo, Edens, & Hart, 2010;Kosson, Smith, & Newman, 1990;Serin, Peters, & Barbaree, 1990). Propensity to criminality is not curtailed while in prison.…”
mentioning
confidence: 99%